La migraña - Alatorre, Antonio, (Letras mexicanas ;, 2012)
In Antonio Alatorre's vast oeuvre, La migraña occupies a special place as the only novel written by this man of letters and to which he dedicated considerable effort. Told through an internal dialogue and from different perspectives, opening up readers eyes, the novel tells the story of Guillermo, a character who sets off on a journey to his adolescence; he is confronted with the moral precepts of religion, the discovery of sex, and life beyond the strict Catholic school education he received. A creative exercise that unmasks an aspect of Alatorre's work that is sure to captivate readers